DEFINITELY VALUE CONCESSIONAL AND CONTINGENT TO PAY MUNICIPAL ELECTRIC - and; and (Municipal economy of cities. Series: «Economy science», 2013)
The technique of passenger survey to determine the relationship of grace and paid contingent on urban electric. The results of the survey on passenger electric transport Sumy.